Applied linguistics beyond postmodernism - Albert Weideman (Acta Academica, 2013)
Applied linguistics clearly has modernist roots, which have steadily been eroded by postmodernist views. Opposites, such as quantitative and qualitative, or positivist and postpositivist, are often used to characterise this intellectual conflict. The current ascendancy of a potentially modernist paradigm, a dynamic or complex systems approach, will be noteworthy for drawing our attention to at least two complex linguistic ideas that have not adequately been analysed in linguistic theory. A foundational, philosophical analysis of such trends, as attempted in this article, should adopt a fittingly humble stance. That kind of humility, however, also applies across paradigms: the arrival of a new paradigm in the field is a timely reminder that enduring domination of a single paradigm in any discipline remains unlikely.